Different schedules of bowel preparation with sodium phosphate lead to different bowel cleansing effects and adenoma detection rates at colonoscopy. Issue 1 (1st December 2014) - Kang, Jui‐Wen; Chuang, Chiao‐Hsiung; Chen, Chiung‐Yu; Cheng, Hsiu‐Chi; Chang, Wei‐Lun; Chen, Wei‐Ying; Cheng, Pin‐Nan; Sheu, Bor‐Shyang
Summary: Background: Adequate bowel preparation is an important quality indicator of colonoscopy. This study validated whether the bowel cleansing quality and adenoma detection rate (ADR) could be different between two bowel preparation schedules in individuals receiving health examinations. Methods: We enrolled individuals who had received a colonoscopy as part of the regimen for their health checkup program with split‐dose phosphosoda for bowel preparation. Prior to December 31, 2012, the second dose of phosphosoda was administered at 10:00 pm before the day of the colonoscopy and the individuals were defined as the 10‐pm group. After January 1, 2013, the schedule was changed to 4:00 am the same day as the colonoscopy and was defined as the 4‐am group. The bowel cleansing quality was assessed using the Aronchick scale. Results: A total of 431 individuals were included, 259 in the 10‐pm group and 172 in the 4‐am group. The 4‐am group individuals had a higher rate of excellent or good bowel cleansing quality as compared with the 10‐PM group (77.3% vs. 22%, respectively; p < 0.001). The ADR was also higher in the 4‐am group than in the 10‐pm group (36% vs. 25.5%, respectively; p = 0.019). Conclusion: Modifying the time schedule of bowel preparation could improve bowel cleansing quality and increase the colonic ADR in a health management center.